Analisis Peran Aplikasi Gojek dalam Mendorong Pertumbuhan Ekonomi Digital di Kota Tanjung Pinang - Nur Selinda (Jurnal Manajemen Bisnis Digital Terkini, 2025)
This study was conducted to evaluate how the Gojek application contributes to the development of the digital economy, especially for Micro, Small and Medium Enterprises (MSMEs) in Tanjung Pinang City. Together with the rapid development of digital technology, Gojek has become a solution for MSMEs in expanding market share, increasing operational efficiency, and easy access to financial services. This research explores qualitative methods that take a case study approach to MSME players who utilize the Gojek application. The research shows that the Gojek application makes a significant contribution to the development of the digital economy of MSMEs in Tanjung Pinang by providing easy access to marketing, delivery of goods, and digital payments. In addition, MSME entrepreneurs in Tanjung Pinang benefit in gaining cost and time efficiency, while increasing revenue from their sales. However, there are still some obstacles that need to be overcome related to technological adjustments, infrastructure limitations, and costs that must be borne by MSME players.